MEMORY, TIME AND SPACE IN THE HYBRID STRUCTURES: MARCEL PROUST AND ORHAN PAMOUK (Journal of Contemporary Philology, 2019)
This study attempts to interpret the function of memory through the structures of hybridized narration in Time Regained, the last volume of Marcel Proust's In Search of Lost Time, and Orhan Pamuk's Istanbul: Memories and the City. The subject's ability to remember is deeply connected to the temporalizing and spatializing acts of these novels. The narratorial subjectivity in both of these texts, constituted by a combination of the novel's fictional elements and the memoir's documentarian tendencies, registers the differences in the passage of time and space as a result of the reconstruction of meaning. They are both treated in relation to the process of recognizing the past. The narration of both novels insists on defeating these aspects of the phenomenal world, and re-conceiving them through a creative approach directed toward the recording of memories and the resisting of the destructive power of time. In both works, the self-analysis of the author plays a key role: a kind of procedure only made possible by the act of writing.
Keywords: subject; memory; time; space; narrativity